Liquid Laws: Extractivism and Unstable Authority - Murphy, Caitlin Rose Sargeant (Osgoode Digital Commons, 2020)
This thesis concerns the co-constitution of extractivism and claims to authority, particularly in contexts where the legal narrative hides the ways that extractivism is facilitated. I examine how law implicitly structures extractivism, as well as how states use extractivism to generate authority. I look at this relationship in the context of international legal debates over the Antarctic Treaty, and a history of extractive interventions by the settler colonial state towards the Murray-Darling River Basin in south-eastern Australia. The way I read claims to authority engages both the violence and instability of these claims. The specific ways in which the relationship between extractivism and authority is enacted in these contexts depends in part on the spatial construction of water and ice. The co-constitution of extractivism and authority in these examples is also revealed both through imperial imaginaries that have material effects, and material practices that build a colonial legal imaginary.